Characterization of the solution heat-treated binary β-type Ti-Mo alloy for bio-implant applications - Netshia Mukhethwa; Phasha Maje; Ngobe Bongani; Olubambi Peter (MATEC Web of Conferences)
There is currently a high demand for biomedical implant materials due to the rapidly growing population of aged people in many countries. Ti-Mo alloys belong to a class of promising examples of beta (β)- type Ti materials containing non-toxic and non-allergic alloying elements that can be used for bio-implant applications. This study focuses on characterizing the solution heat-treated binary β Ti-14Mo alloy manufactured using the vacuum arc melting technique. All heat-treated samples resulted in dual phase structure comprised of β and α″ phases. As detected from XRD analysis, the intensity of the orthorhombic (α″) martensite phase increased with a decrease in heat-treated temperature. However, the samples heat-treated at 1100℃ yielded the highest hardness compared to those at 1000 and 900℃, respectively. Evidenced by micrographs, this high hardness is attributed to the degree of fineness of the α″ sub-structures that nucleated within the large β grains. The results show that the different solution heat treatments influence the structure of materials and mechanical properties.